Storeys of emptiness: an ethnography of empty homes In London - Mukherji, M (2020)
Based on 12 months of ethnographic research in a luxury square and a council estate in Chelsea, London, this thesis questions widespread conceptualisations of empty homes as sites of decay and decline associated with a loss of community. I combine current debates about the transformation of homes into financial assets with the latest material culture approaches to land, belonging and the home, to offer unique insights into everyday experiences of living alongside empty homes. Through rituals and practices such as gardening, visiting the nearby cemetery, drawing family trees and carol singing, the participants in my research created strong feelings of belonging and identity amidst flows of capital and the financialisation of housing. By focusing on specific creative practices that residents engage in to battle or conceal emptiness across the two sites, the thesis extends beyond the policy-oriented approach of “solving” the problem of emptiness, while allowing for a critical interrogation of which homes fall within this problematisation in the first place. I argue that the perceived emptiness is less about absence and more about neglect towards particular forms of care. By paying close attention to practices of care and the trope of the community that is evoked across both my sites, my research transcends any simplistic binary narrative of emptiness as absence or crisis and reveals instead how the concept is linked with deeply ingrained patterns of ownership, cycles of renewal and long-lasting relationships to land.